An increasing mutual promotion of economic growth between China and the world observed from nighttime light remote sensing - Zuoqi Chen; Xiaojun You; Congxiao Wang; Wenting Wu; Ye Wei; Kaifang Shi; Bailang Yu (International Journal of Digital Earth)
Assessing the promotion of economic growth between China and the world is challenging given data limitations and the lack of consideration of time delay. Based on the time-series nighttime light (NTL) data from satellites covering more than 100 months, we found that the world is lighting in most countries, even after a sudden jump due to the outbreak of COVID-19. Then, we conducted the convergent cross-mapping before COVID-19 (2014.1-2019.12) and during/after COVID-19 (2020.1-2022.11), we found that the influences from China to the world economic growth in these two phases are widely expanded to more and more economies, the number of which increases from 65 to 73, with a longer time lag, which averagely increased from 4.6 to 6.6 months. On the contrary, the number of economies, which can influence China’s economy, is increasing from 48 to 55 but the average lag time is stable at around 4.5 months. Meanwhile, a regional multilateral economic network related to China’s economy was found. The economies with mutual causalities with China were mostly concentrated in Asia, Africa, and Europe. China indeed can warm the world economy partially, especially in developing countries and has also benefited from the multilateral economy.